Epigenetics of the preferential silencing of Brachypodium stacei-originated 35S rDNA loci in the allotetraploid grass Brachypodium hybridum - Natalia Borowska-Zuchowska (Nature Portfolio, 2017)
Abstract Nucleolar dominance (ND), initially described as ‘differential amphiplasty’, is a phenomenon observed in some plant and animal allopolyploids and hybrids in which the selective suppression of the activity of 35S rRNA gene loci that have been inherited from one of the two or more ancestral genomes occurs. Although more than 80 years have passed since the discovery of ND, there is still a significant lack in our understanding of the mechanisms that determine this phenomenon. Here, we aimed to investigate the epigenetic status of 35S rRNA gene loci in the monocotyledonous Brachypodium hybridum, which is an allotetraploid that has resulted from a cross between B. distachyon and B. stacei. We revealed that the repressed B. stacei-inherited rDNA loci are characterised by a high level of DNA methylation. The global hypomethylation of B. hybridum nuclear DNA induced by 5-azacytidine, however, seems to be insufficient for the transcriptional reactivation of these loci, which indicates that factors other than DNA methylation are behind the suppression of B. stacei-originated loci. We also showed that the transcriptionally active and silenced fractions of rRNA genes that had been inherited from B. distachyon occupy different domains within the chromocentres adjacent to the nucleolus, depending on their epigenetic status.